Pengaruh Persepsi Manfaat, Kepercayaan dan Persepsi Risiko Terhadap Minat Menggunakan Mobile Banking pada Nasabah Bank BCA di KCU Margonda Depok - Ahmad Nurholis; Salman Paludi (Human Capital Development, 2023)
The purpose of this study was to determine the effect of perceived benefits, trust, and perceived risk on the intention to use mobile banking for customers of Bank BCA KCU Margonda Depok. The population in this study were customers of Bank BCA KCU Margonda Depok with a total sample of 100 respondents. This study uses the accidental sampling method by distributing online questionnaires that have been tested for validity and reliability. To analyze the data of this study using SPSS version 24. The results of this study partially indicate that perceived benefits and trust have a positive and significant effect on intention to use. While the perception of risk has no influence on the intention to use. Simultaneously, the perceived benefits, trust and perceived risk variables have a significant effect on the intention to use.